2018
DOI: 10.1002/jsfa.8903
|View full text |Cite
|
Sign up to set email alerts
|

Bitter taste masking of enzyme‐treated soy protein in water and bread

Abstract: Bitter-masking effects were generally more discernible in the aqueous model compared with the bread model. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
(71 reference statements)
1
12
0
1
Order By: Relevance
“…Bitterness of protein hydrolysates can be masked by mixing with different food additives, including cyclodextrin, maltodextrin, polyphosphate, etc. (Saha & Hayashi, ; Bertelsen et al ., ). Furthermore, a number of bitter taste inhibiting agents are capable of suppressing bitter perception (Ley, ), such as sweeteners and flavours.…”
Section: Recent Developments In Debittering Of Protein Hydrolysates Fmentioning
confidence: 97%
“…Bitterness of protein hydrolysates can be masked by mixing with different food additives, including cyclodextrin, maltodextrin, polyphosphate, etc. (Saha & Hayashi, ; Bertelsen et al ., ). Furthermore, a number of bitter taste inhibiting agents are capable of suppressing bitter perception (Ley, ), such as sweeteners and flavours.…”
Section: Recent Developments In Debittering Of Protein Hydrolysates Fmentioning
confidence: 97%
“…Studies on techniques for debittering by‐products, or residues, of natural origins have been gathering considerable attention since if this is removed, this threshold barrier, could be used for food technologies as various final products. Therefore, strategies that have been used to debitter includes mixing with different food additives (Bertelsen, Laursen, Knudsen, Møller, & Kidmose, 2018), sweeteners, by the usage of Maillard reaction (Hong, Ndagijimana, & Betti, 2016) and most commonly by the encapsulation technology (Holgado, Márquez‐Ruiz, Ruiz‐Méndez, & Velasco, 2019; Khan et al, 2019) as it avoids exposure of bitter compounds to bitter taste receptors.…”
Section: Introductionmentioning
confidence: 99%
“…SP contains all of the essential amino acids and also offers a good balance among nonpolar amino acid, polar amino acid and charged amino acid. SP has been investigated as the food additives, water emulsions and nutraceutical encapsulation in the form of nanoparticles, microspheres and hydrogels 20-23. It was reported that the hydrolysate of SP had the ability to inhibit angiotensin I-converting enzyme (ACE) which could be used to treat hypertension 24 and the ACE inhibition peptides derived from SP could lower blood pressure of spontaneously hypertensive rats 25.…”
Section: Introductionmentioning
confidence: 99%